The Results of a 2-Year Randomized Trial of a Worksite Weight Management Intervention - Williams, Andrew E. (Am J Health Promot, 2014)
PURPOSE: We assessed the effectiveness of a worksite management intervention (the 3W program) for overweight and obese hotel employees. DESIGN: The program was tested in a 2-year cluster-randomized trial involving 30 hotels that employed nearly 12,000 individuals. SETTING: All participating hotels were on Oahu, Hawaii. The intervention was implemented within hotel worksites. SUBJECTS: Participants were included in the analysis if they had an initial body mass index (BMI) ≥ 25, were assessed at least twice, were not missing other data needed for the analysis, and did not switch to employment at a hotel in a different experimental condition. Of the 6519 employees we assessed, data from 1207 individuals (intervention: 598; control: 610) met these criteria and contributed to the analysis. INTERVENTION: The intervention had two components: (1) group meetings and (2) a workplace environment intervention. MEASURES: Weight and waist to height ratio (WHtR) were measured at three annual assessments. ANALYSIS: The effect of the intervention on change in BMI and WHtR was estimated in hierarchical mixed regression models using full maximum likelihood to estimate model parameters. RESULTS: The effects on change in BMI and WHtR were in the expected direction but were not statistically significant. CONCLUSION: The 3W program was not effective. The low intensity of the intervention may have contributed to its ineffectiveness.